Body language on the pitch: insights into soccer players` nonverbal behavior at the FIFA men`s World Cup 2022 - Lian, I.; Gjesdal, S.; Fletcher, Y.; Jordet, G. (Frontiers in Psychology, 2026)
Communication is an important aspect in team sports, yet there is a lack of studies looking at intrateam communication during performance. The aim of this study was therefore to explore soccer players` use of nonverbal behavior (NVB) at the FIFA men`s World Cup 2022. A total of 18,031 distinct NVBs were registered for 143 individual players from 33 games, representing all 32 participating national teams. NVB was divided into tactical and emotional categories. Several statistical tests were performed to investigate the relationship between NVB and potential constraints (e.g., game stage, game halves, roles in a team, geographical location of the national team). The results showed that players displayed more tactical than emotional NVB, and more negative than positive emotional NVB. Moreover, there were differences in NVB expression based on positional roles, but not between captains and other players. NVB expressions changed throughout a game but did not differ between group stage games and knockout games. There were no differences in NVB expressions based on the end result of a game. The findings provide the first empirical examination of quantified NVB of soccer players from the World Cup context. The methodology and findings can be useful for soccer managers, psychologists, researchers and analysts to include psychological measures into game analyses.